Increasing volume of food by incorporating air reduces energy intake*. (2014) - Serisier, Samuel; Pizzagalli, Anthony; Leclerc, Lucie; Feugier, Alexandre; Nguyen, Patrick; Biourge, Vincent; German, Alexander J.
Abstract: Major challenges with weight management using weight-loss diets include hunger and rapid consumption of food, both of which lead to poor owner compliance. The aim of the present study was to determine the effect of increasing volume, by incorporating air, into dry expanded food, on satiety in dogs. Three studies have been performed. The first study aimed to measure the effect of volume of food on meal duration in dogs fed at their maintenance energy requirement. The purpose of the second study was to determine the effect of volume of food on satiety. The aim of the third study was to compare the satiety effect of the test diet with a maintenance dry diet commonly used in adult dogs. Throughout the studies, faecal score remained optimal. As volume of diet increased, the duration of food intake significantly increased ( P < 0·001) and energy intake significantly decreased ( P = 0·012). The present study has demonstrated that incorporating air into food to increase the volume of diet induces a satiety effect, independent of macronutrient profile, possibly by slowing food intake. Consequently, incorporating air into food might be a useful strategy for weight management in companion animals.